Lanthanum–titanium oxide composite from a single molecular cluster: Non-enzymatic mesoporous electrochemical nitrite ion sensor - Mansoor, Muhammad Adil; McKee, Vickie; Yusof, Farazila; Lim, S.P.; Zubir, Mohd Nashrul Mohd; Ming, Huang Nay; Mazhar, Muhammad Ehsan (Elsevier, 2018)
In the present investigation, lanthanum–titanium [La3Ti6O4(OH)6(C2F3O2)13(H2O)2(C4H8O)6] (1) was successfully used as single source precursor to fabricate electrodes of LTO 600 (La4Ti9O24-La2O3-LaTiO3-TiO2(rutile)) and LTO 700 (La4Ti9O24-La2O3) at sintering temperature of 600 and 700 °C, respectively. The X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) have been used to determine the phase purity and oxidation states of the elements present in the samples. Nitrogen adsorption/desorption isotherms are used to investigate the Brunauer, Emmett, and Teller (BET) surface area and the Barrett–Joyner–Halenda (BJH) pore size distribution of LTO 600 and LTO 700. The BET analysis revealed pore sizes of 8.7 and 9.9 nm for LTO 600 and LTO 700, respectively, transmission electron microscopy (TEM) revealed the particles are irregular in shape with size range of 55–150 and 145–155 nm for LTO 600 and LTO 700, respectively. The LTO 700 modified glassy carbon electrode (GCE) was used for the elecrtrochemical oxidation of NaNO2 and it showed a better electrocatalytic performance towards the oxidation of NaNO2 than LTO 600. The larger pore size found at the higher sintering temperature could enhance the sensing performance with the limit of detection (LoD) of 0.0151 µM. Furthermore, the composite modified electrode (LTO 700) showed high selectivity towards the detection of nitrite ions in the presence of the common salts. Therefore, the fabricated LTO 700 electrode is a potential candidate for monitoring the toxic nitrite ions levels in edibles, additives and drinking water.